Causal relationship between material price fluctuation and project’s outturn costs - Olatunji, Oluwole; Orundami, A.; Ogundare, O. (Emerald Group Publishing, 2018)
Purpose: A section of project management literature attributes overruns to estimators’ deceit and delusion. An example of this is Flyvbjerg’s theorisation of strategic misrepresentation and optimism bias. To show that such a notion is not true entirely, the study elicits evidence relating to how costs of projects often fluctuate erratically as prices of construction materials change throughout contract cycle times. The purpose of this paper is to examine the causal relationships between persistent changes in prices of construction materials and project’s outturn costs. Design/methodology/approach: The authors obtained and analysed price data of construction materials published in a Nigerian national daily in the 16 years between 2000 and 2015. Additional data were obtained from a quantity surveying firm to validate the archival data on material prices, and to compare the firm’s robust database of project estimates and the corresponding outturn costs of specific building elements (detailed in the study). The goal of the analysis is to explore spontaneity and causal impact in the relationship between changes in prices of construction materials and project costs. Kolmogorov-Smirnov and Anderson-Darling tests were used to obtain the probability distributions of the causal relationships. Findings: Findings show disproportionate positive correlations between changes in material prices and outturn costs in Nigeria. An important dimension to this, however, is that although fluctuations in material costs often trigger variations to project costs, outturn price only accounts for about one-third of actual cost variability. Recovery of costs, not least profit making, under these conditions is a complex process. Originality/value: This paper concludes that dynamism in cost attributes is neither a deceit nor a delusion; understanding and tolerating them is not a systemic weakness, rather an essential key to project success and stakeholder satisfaction. Findings from the study also bring measured certainties to the transformation of variable costs into fixed price outcomes, an important consideration that will help contract estimators and project managers to understand the likelihood of fluctuation in material costs and how these might trigger variability in project costs.